Tabrīz, Iran. Ilkhanid Tabrīz. Architectural and Archaeological Research on the Rabʿi Rashīdī. Season 2019 - Lorain, Thomas; Fuchs, Christian; Korn, Lorenz (e-Forschungsberichte des DAI, 2022)
This article presents preliminary results of the 2019 archaeological campaign on the Rabʿi Rashīdī archaeological site in Tabrīz (Iran). The work undertaken included a geophysical survey, limited excavations as well as an architectural and topographical survey of the whole site. While excavations show for the first time structural remains from the Ilkhanid period (ie early 14th century) and their connections with later occupation, the topographical and architectural survey of the whole site bring new light on its organisation and fortification as well as new questions on specific structures and their meanings.